2023
DOI: 10.1021/acssuschemeng.2c05826
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Oxygen Reduction Reaction Electrocatalytic Activity of Postsynthetically Modified Covalent Organic Frameworks

Abstract: The pyrolysis of organic precursors to produce heteroatomic-doped carbonaceous materials has emerged as a powerful tool to construct metal-free heterogeneous electrocatalysts due to their low cost and their environmental friendliness. However, the lack of control in the atomic positions or the location of the chemical functionalities makes it difficult to establish structure–property relationships. Herein, we report an easy strategy to compare the electrocatalytic oxygen reduction reaction (ORR) performance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…The rate-determining step (RDS) is the step with the largest Δ G n value for the four-electron process. 41 The free energy profiles of the OER on VCoS indicated that the RDS was the one-step formation of OOH*, with VCoS having a smaller Δ G n value of 1.57 eV compared to MoCoS (1.79 eV) (Fig. 3(b)), and the free energy value of CoS is 1.66 eV (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…The rate-determining step (RDS) is the step with the largest Δ G n value for the four-electron process. 41 The free energy profiles of the OER on VCoS indicated that the RDS was the one-step formation of OOH*, with VCoS having a smaller Δ G n value of 1.57 eV compared to MoCoS (1.79 eV) (Fig. 3(b)), and the free energy value of CoS is 1.66 eV (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Zhang et al proposed an optimal transition metal for producing single-atom catalysts (SAC) with COFs. DFT calculations were performed in this study [129] . These calculations suggested that the transition metals bind to the N site, Ni, and Co, lowering the Gibbs energy barrier for the OER.…”
Section: Oermentioning
confidence: 99%
“…Typically, they possess precisely controllable monomers, large specific surface area, and high stability, which make them an efficient platform for electrocatalysis [ 27 , 28 , 29 ]. Specifically, the remarkable advantages of COFs have received widespread attention in electrocatalytic ORR [ 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. The large specific surface area and porous nature of COFs can provide sufficient active sites to participate in the catalytic reaction [ 37 ].…”
Section: Introductionmentioning
confidence: 99%